Nessler Method Verification for Determining Ammonia in Shrimp Pond Wastewater and Its Application in the Ammonia Adsorption Test with Lampung Natural Zeolite - Ni Luh Gede Ratna Juliasih; Lia Madyo Ratri; Andi Setiawan; Mita Rilyanti; Rinawati Rinawati; Agung Abadi Kiswandono; Fitri Kurniawati (ALCHEMY Jurnal Penelitian Kimia, 2024)
Ammonia levels exceeding 0.50 mg/L can threaten organisms in aquatic environments. The Nessler method is one of the ammonia analysis methods based on the reaction between ammonia in a basic solution and Nessler reagent (K2HgI4), forming a colloidal dispersion with a brownish-yellow colour. The colour intensity is determined by spectrophotometry. This research aims to verify the Nessler method for determining ammonia levels in shrimp pond wastewater. The research results indicate that the Nessler method shows good linearity in the range of ammonia concentrations from 1 to 5 mg/L, with a correlation coefficient (R2) value of 0.9962. The precision value was determined from repeatability, expressed as %RSD (Relative Standard Deviation), i.e., 1.92%, and it meets acceptance criteria, which should be less than 0.5 of the Horwitz RSD. The accuracy obtained from the standard addition method provides a percentage recovery value of 99.25%, meeting the AOAC acceptance criteria. The detection limit and quantification limit of the technique are 0.3883 mg/L and 1.2943 mg/L, respectively. The verified method is then applied to analyze shrimp pond wastewater samples from Sriminosari Village, East Lampung, resulting in an ammonia concentration of 1.52 mg/L. The ammonia levels were then reduced by adsorption with natural zeolite Lampung, decreasing ammonia levels by 20.30%. Meanwhile, adsorption with an activated zeolite reduced the ammonia levels by 45.30%.